A honokiol-mediated robust coating for blood-contacting devices with anti-inflammatory, antibacterial and antithrombotic properties. Issue 47 (22nd November 2021) - Li, Linhua; Chen, Chong; Zhang, Chunle; Luo, Rifang; Lan, Xiaorong; Guo, Fan; Ma, Liang; Fu, Ping; Wang, Yunbing
Abstract : A robust and superior honokiol-mediated coating was constructed by a simple, economical and efficient method. The honokiol modified coating possess excellent and long-term anti-inflammatory, anti-infection and anti-thrombotic properties. Abstract : Thrombus, bacterial infections, and severe inflammation are still serious problems that have to be faced with blood-contacting materials. However, it is a great challenge to simultaneously meet the above functional requirements in a simple, economical and efficient method. As such, we put forward a robust and versatile coating strategy by covalently modifying the multi-pharmacological drug honokiol (HK) with an amine-rich polydopamine/polyethyleneimine coating, through which anticoagulant, antibacterial and anti-inflammatory properties were obtained (DPHc) simultaneously. The amine content in the DPHc coating was lower than the detection limit, while it contained abundant phenolic hydroxyl groups (49 μmol cm −2 ). Meanwhile, the 30 day drug release test confirmed that the drug was firmly modified on the surface of the coating without release. A systematic in vitro and ex vivo evaluation confirmed that the coating had significant anti-thrombotic properties. The antibacterial rates of the DPHc coating against Staphylococcus aureus and Escherichia coli reached 99.98% and 99.99%, respectively. In addition, subcutaneous implantation indicated that the DPHc coating also has excellent histocompatibility. To the best of our knowledge, this is the first study using HK as a coating material that can not only combat thrombosis and infection but also significantly inhibit inflammation associated with the use of blood-contacting materials, thus expanding the application of HK in the field of biomaterials.